Control Of 3d Printer Using Drone With Autopilot And Raspberry Pi Microcontroller - Sam, Jun Kok (Universiti Sains Malaysia, 2019)
Rapid prototyping or 3D printing technology is the advanced manufacturing process and it is getting popular to many sectors of field. However, there are some limitation of this technology which is limited to the printer size. This study focuses on combining of drone technology and rapid prototyping technology. Therefore, control the 3D printer using drone that paired with autopilot and microcontroller can build an object without considering the size of printer. The conversion of tool path to the flight path is done. Two flight paths for printing a rectangular sheet with size of 2m×8m and 20m×80m are generated. The simulation results show the flight path with size of 2m×8m is better than flight path with size of 20m×80m. However, this is concern to the resolution of global positioning system. This paper has made a big step toward the idea of combining the 2 technologies.